2018
DOI: 10.1136/emermed-2017-206997
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-triggered therapy for assessment and management of alcohol withdrawal syndrome in the emergency department short-stay clinical decision unit

Abstract: IntroductionWe previously reported that benzodiazepine detoxification for alcohol withdrawal using symptom-triggered therapy (STT) with oral diazepam reduced length of stay (LOS) and cumulative benzodiazepine dose by comparison with standard fixed-dose regimen. In this study, we aim to describe the feasibility of STT in an emergency department (ED) short-stay clinical decision unit (CDU) setting.MethodsIn this retrospective cohort study, we describe our experience with STT over a full calendar year (2014) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Seizures in ED before treatment 3/394 (0.8%) * effect size : −0.03 (95% CI: −1.7 to 1.5) 4/504 (0.8%) 3. ED length of stay (non-admitted patients) Median 266 min (IQR 163 to 387) effect size: −33 (95% CI: −75 to −6) Median 299 min (IQR 192 to 463) Symptom-triggered therapy Ismail MF, Doherty K, Bradshaw P, O’Sullivan I, Cassidy EM (2019) [ 33 ] Adults with AWS (clinician assessment) placed on treatment protocol in a short stay clinical decision unit Symptom-triggered diazepam (route not specified) when CIWA ≥10 ( n = 174) N/A 1. Cumulative diazepam dose Median 20 mg (IQR 80) N/A Serious 2.…”
Section: Resultsmentioning
confidence: 99%
“…Seizures in ED before treatment 3/394 (0.8%) * effect size : −0.03 (95% CI: −1.7 to 1.5) 4/504 (0.8%) 3. ED length of stay (non-admitted patients) Median 266 min (IQR 163 to 387) effect size: −33 (95% CI: −75 to −6) Median 299 min (IQR 192 to 463) Symptom-triggered therapy Ismail MF, Doherty K, Bradshaw P, O’Sullivan I, Cassidy EM (2019) [ 33 ] Adults with AWS (clinician assessment) placed on treatment protocol in a short stay clinical decision unit Symptom-triggered diazepam (route not specified) when CIWA ≥10 ( n = 174) N/A 1. Cumulative diazepam dose Median 20 mg (IQR 80) N/A Serious 2.…”
Section: Resultsmentioning
confidence: 99%
“…1 7 These units, often staffed with a midlevel practitioner and supervised by ED attending staff, were originally developed to monitor patients presenting with chest pain but low clinical probability of myocardial infarction, with the goal of using fewer resources than the analogous admission to a cardiac ICU. 8 Subsequent data have shown that EDOUs can reduce inpatient admission rate, length of stay, and cost for a wide variety of acute medical problems [9][10][11][12][13][14] and the Institute of Medicine has concluded that EDOUs can reduce unwarranted hospitalizations and improve institutional patient flow. 15 Despite this, few studies have evaluated EDOU protocols for acute neurological presentations.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 One descriptive retrospective chart review (n = 174) reported that patients placed on a symptomtriggered benzodiazepine protocol received a median cumulative diazepam dose of 20 mg (IQR 80 mg), and 97.1% were ultimately discharged from the ED, although they did not have a comparison group. 30 Another retrospective chart review (n = 99) compared those placed on a CIWA-based symptom-triggered protocol with a non-matched comparison group that received a standard tapered benzodiazepine regime. 31 The symptom-triggered group received lower cumulative benzodiazepine doses (median 80 mg vs. 170 mg, p = 0.000), and had shorter lengths of stay (median 2 days vs. 3 days, p = 0.006).…”
Section: Symptom-triggered Therapymentioning
confidence: 99%
“…29 Symptom-triggered protocols have been implemented in EDs with clinical decision units that can support longer stays, although patient outcomes have not been rigorously evaluated. 30,31 One retrospective chart review suggested that a symptom-triggered protocol may decrease total doses of benzodiazepines administered, however, this nding would need to be replicated in a prospective, controlled study. 31 Existing studies do not show uniform evidence of bene t of phenobarbital (used alone, or in conjunction with symptom-triggered benzodiazepines) in multiple assessed outcomes: ICU admission, ED length of stay, and complications such as intubation.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation